Optimal Taxation in Search Equilibrium with Home Production - Per Engström; Bertil Holmlund; Ann-Sofie Kolm (Uppsala University, Department of Economics, 2001)
The paper develops a two-sector general equilibrium search model where goods are produced exclusively in the market and services are produced both in the market and within the households. We use the model to examine how unemployment and welfare are affected by labor taxes in general and sectoral tax differentiation in particular. We find that a tax cut on services reduces unemployment whereas a tax cut on goods has no effect. A reform involving tax differentiation, with lower taxes on services, is welfare improving. Numerical calibrations of the model suggest that the welfare gains from tax differentiation are large if the government absorbs a substantial fraction of GDP.
Keywords: H21; J22; J41; J64; 330; Taxation; Home production; Search; Unemployment; Optimale Besteuerung; Verbrauchsteuer; Arbeitsplatzsuchmodell; Theorie der Arbeitslosigkeit; Mehr-Sektoren-Modell; Haushaltsproduktion; Allgemeines Gleichgewicht; Theorie